2006
DOI: 10.1016/j.jeurceramsoc.2005.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CeO2 on the sintering behaviour, cation order and properties of Ba3Co0.7Zn0.3Nb2O9 ceramics

Abstract: The effect of low-level CeO 2 addition and cooling rate on sintering, microstructures, phase formation, 1:2 ordering and microwave dielectric properties of Ba 3 Co 0.7 Zn 0.3 Nb 9 (BCZN) was investigated. It was found that low levels doping of CeO 2 (up to 0.5 wt.%) could significantly improve densification of the specimens and their properties. Dielectric properties of CeO 2 -doped samples were sensitive to 1:2 ordering in the B-site. Slow cooling after sintering improved the unloaded quality factor (Q × f va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
4
28
0
Order By: Relevance
“…This improvement of the Q f -value is explained by 1:2 cation ordering in accordance with the XRD data recorded on the surface of the post-sinter annealed ceramics (S1a and S2a), as shown in the small insert figure in Figures 3b and 5b, respectively. A similar result was previously reported which shows the increase of the Q f values as a consequence of cation ordering [9]. This Q f value of 123,700 GHz is higher than those obtained for the undoped and Al 2 O 3 -doped BCZN ceramics (Q f = 115,307 and 61,056 GHz, respectively), published recently [14,15], indicating that the Ba(Co 0.7 Zn 0.3 ) 1/3 Nb 2/3 O 3 materials are promising candidates for microwave device applications.…”
Section: Microwave Dielectric Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…This improvement of the Q f -value is explained by 1:2 cation ordering in accordance with the XRD data recorded on the surface of the post-sinter annealed ceramics (S1a and S2a), as shown in the small insert figure in Figures 3b and 5b, respectively. A similar result was previously reported which shows the increase of the Q f values as a consequence of cation ordering [9]. This Q f value of 123,700 GHz is higher than those obtained for the undoped and Al 2 O 3 -doped BCZN ceramics (Q f = 115,307 and 61,056 GHz, respectively), published recently [14,15], indicating that the Ba(Co 0.7 Zn 0.3 ) 1/3 Nb 2/3 O 3 materials are promising candidates for microwave device applications.…”
Section: Microwave Dielectric Propertiessupporting
confidence: 90%
“…No significant differences in dielectric properties were observed before and after polishing. This is due to their good microwave dielectric properties [9]. This observation suggests that the secondary phases of Ba 8 (Co,Zn) 1 Nb 6 O 24 and of Ba 5 Nb 4 O 15 seem to have no effect on the dielectric properties.…”
Section: Microwave Dielectric Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…The s f values in our work also increased with increasing doping content. According to published literature [5,27], we can rational assume that the s f value of BCZN phase is nearly 0 ppm/°C. When the doping amount increased from 0 to 0.06, the SEM (EDS) results above indicated that the increase of s f value can be owing to the relatively increasing amount of secondary phase Ba 8 CoNb 6 O 24 , reportedly having a positive s f value of nearly 14 ppm/°C [32], which can reasonably explain the rising trend of the s f value with increasing Y 2 O 3 doping in the Ba(Co 0.6 Zn 0.38 ) 1/3 Nb 2/3 O 3 solid solution.…”
Section: Resultsmentioning
confidence: 98%
“…Azough et al [27] reported that perfect properties of 0.7BZN-0.3BCN (e r = 34.5, Q 9 f = 97000 GHz, s f * 0) ceramics have been developed under slowly annealing condition of 60°C/h with 0.4 wt% CeO 2 addition. Ba(Ga 1/ 2Ta 1/2 )O 3 -doped BZN ceramics have been prepared by the mixed oxide route, achieving good microwave dielectric characteristics of e r = 37 and Q 9 f = 90,469 GHz [28], but the s f value was not clear.…”
Section: Introductionmentioning
confidence: 99%